2013
DOI: 10.7213/academica.011.002.ao06
|View full text |Cite
|
Sign up to set email alerts
|

EPIDEMIOLOGIA DA IMUNODEFICIÊNCIA VIRAL, LEUCEMIA VIRAL E PERITONITE INFECCIOSA EM FELINOS PROCEDENTES DE UM HOSPITAL VETERINÁRIO Epidemiology of viral immunodeficiency, viral leukemia and infectious peritonitis in cats from a veterinary hospital

Abstract: Interessa compreender a epidemiologia da imunodeficiência viral felina (FIV), leucemia viral felina (FeLV) eperitonite infecciosa felina (PIF). Para tanto, realizou-se estudo descritivo retrospectivo em gatos atendidospor um hospital universitário na cidade de São Paulo. Entre 4.357 atendimentos, foram confirmados 99 casos para uma das doenças infecciosas estudadas. Para o diagnóstico da infecção pelo FIV e FeLV, utilizou-se o teste imunoenzimático (ELISA). Consideraram-se positivos os gatos que apresentavam a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
4
3
2
3
Order By: Relevance
“…The prevalence of 12.32% for FIV and 5.80% for FeLV in Fortaleza-CE varied from the results found, through serological methods, in other cities of Brazil: 0.78% and 0.36% in São Paulo (Santos et al, 2013), 5.63% and 0.33% in Araçatuba-SP (Sobrinho et al, 2011) for FIV and FeLV, respectively, and 38.3% in Pelotas and Rio Grande-RS for FeLV (Meinerz et al, 2010). Felines with FIV and FeLV detected by PCR or nested PCR were 4.14% and 47.0% in Belo Horizonte (Teixeira et al, 2007;Coelho et al, 2011), respectively, and 15.70% for FIV in Pelotas -RS (Silva et al, 2014), and there was no presence of co-infection of these diseases in these studies.…”
Section: Discussioncontrasting
confidence: 62%
“…The prevalence of 12.32% for FIV and 5.80% for FeLV in Fortaleza-CE varied from the results found, through serological methods, in other cities of Brazil: 0.78% and 0.36% in São Paulo (Santos et al, 2013), 5.63% and 0.33% in Araçatuba-SP (Sobrinho et al, 2011) for FIV and FeLV, respectively, and 38.3% in Pelotas and Rio Grande-RS for FeLV (Meinerz et al, 2010). Felines with FIV and FeLV detected by PCR or nested PCR were 4.14% and 47.0% in Belo Horizonte (Teixeira et al, 2007;Coelho et al, 2011), respectively, and 15.70% for FIV in Pelotas -RS (Silva et al, 2014), and there was no presence of co-infection of these diseases in these studies.…”
Section: Discussioncontrasting
confidence: 62%
“…The prevalence of FIP (3.7%; 19/520) identified during this investigation was similar to that observed in other reports from Brazil, where a prevalence of 1.12% (49/4,357) was described in São Paulo (SANTOS et al, 2013) and 2.03% (13/638) in Rio Grande do Sul (OLIVEIRA et al, 2003). Epidemiological studies done in other countries have revealed prevalence levels of FIP that varied between 0.52% (60/11,535) in Raleigh, North Carolina, USA (PESTEANU-SOMOGYI et al, 2006), and in 1.41% (231/16,275) from Munich, Germany (RIEMER et al, 2016).…”
Section: Discussionsupporting
confidence: 77%
“…Epidemiological studies done in other countries have revealed prevalence levels of FIP that varied between 0.52% (60/11,535) in Raleigh, North Carolina, USA (PESTEANU-SOMOGYI et al, 2006), and in 1.41% (231/16,275) from Munich, Germany (RIEMER et al, 2016). The prevalence levels identified in Brazil might be related to the fact that cat owners do not frequently submit their pets for necropsy evaluation at veterinary hospitals due to financial constraints (SANTOS et al, 2013), which probably underestimates the prevalence of this disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations